2021
DOI: 10.21037/tp-21-12
|View full text |Cite
|
Sign up to set email alerts
|

Case report of juvenile polyposis/hereditary hemorrhagic telangiectasia syndrome: first report in Korea with a novel mutation in the SMAD4 gene

Abstract: Juvenile polyposis/hereditary hemorrhagic telangiectasia (JPS/HHT) syndrome is a rare, autosomal dominant disorder caused by mutations in the SMAD4 gene, presenting with features of both juvenile polyposis syndrome (JPS) and HHT. Reports and studies of JPS/HHT syndrome are mostly from Western countries, while there are scarce reports from East Asian countries. We report a case of a Korean boy who had been previously diagnosed with JPS at 7 years and had first visited to our center at 15 years of age. Genetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…3 SMAD4 mutations cause juvenile polyposis overlap with HHT (JPHT). 5 HHT-1 is associated with earlier onset of the disease and has vascular malformations in the lungs and brain predominately. HHT-2 has a later onset with vascular malformations in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…3 SMAD4 mutations cause juvenile polyposis overlap with HHT (JPHT). 5 HHT-1 is associated with earlier onset of the disease and has vascular malformations in the lungs and brain predominately. HHT-2 has a later onset with vascular malformations in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al . 12 reported a case in South Korea of a hereditary hemorrhagic patient with blood capillary dilation and juvenile polyposis. The patient’s frequent nose bleeding occurred at the age of 5 and JPS symptoms began at the age of 7 years; 30–50 colon polyps were observed.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…In 2012, O'Malley and associates studied and determined the prevalence and clinical manifestations of HHT in their juvenile polyposis patients and concluded that nearly all have the overlap syndrome and that healthcare providers must be aware and cognizant of the juvenile polyposishemorrhagic hereditary telangiectasia overlap syndrome [10]. In 2021, the first case of JPS-HHT in South Korea was reported (a 15-year-old boy), exhibiting the performed genetic studies of the patient himself and his parents revealing the detection of a de novo variant in the SMAD4 gene, [SMAD4 c.1146_1163del; p. His382_Val387del] [12]. This report recommended that JPS patients should undergo genetic evaluation of associated genes, including SMAD4, and those patients who are genetically confirmed with SMAD4 variants ought to undergo the appropriate evaluation to detect coexisting asymptomatic AVMs and avert life-threatening complication(s) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, the first case of JPS-HHT in South Korea was reported (a 15-year-old boy), exhibiting the performed genetic studies of the patient himself and his parents revealing the detection of a de novo variant in the SMAD4 gene, [SMAD4 c.1146_1163del; p. His382_Val387del] [12]. This report recommended that JPS patients should undergo genetic evaluation of associated genes, including SMAD4, and those patients who are genetically confirmed with SMAD4 variants ought to undergo the appropriate evaluation to detect coexisting asymptomatic AVMs and avert life-threatening complication(s) [12].…”
Section: Introductionmentioning
confidence: 99%